Disrespected employees are quitting what can managers do differently? : new modes of working require managers to adapt the ways they signal respect for employees - Rogers, Kristie; Schinoff, Beth (MIT Sloan Management Review, 2022)
The typical signals of respect largely necessitate in-person interaction. They are subtle, easier to provide in informal settings, and contagious to others when everyone is in the same physical space -- conditions that are more difficult to replicate in virtual settings. To effectively show respect for a remote workforce, managers should use time, validate employee performance, send tangible respect signals, and offer visibility for employees and their work.
Keywords: Corporate culture; Work environment; Employee morale; Organizational behavior; Personnel management; Culture organisationnelle; Personnel; Moral; Comportement organisationnel; Personnel; Direction